2010
DOI: 10.1021/ja1078943
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Nanocolloids

Abstract: Graphene oxide (GO) nanocolloids-sheets with lateral dimension smaller than 100 nm-were synthesized by chemical exfoliation of graphite nanofibers, in which the graphene planes are coin-stacked along the length of the nanofibers. Since the upper size limit is predetermined by the diameter of the nanofiber precursor, the size distribution of the GO nanosheets is much more uniform than that of common GO synthesized from graphite powders. The size can be further tuned by the oxidation time. Compared to the microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
317
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(331 citation statements)
references
References 34 publications
10
317
0
4
Order By: Relevance
“…GO membranes with different IL spacing were prepared by storing them in a sealed container with different RH of 0%, 12%, 33%, 75%, 84% and 100%. To this end, we used saturated solutions of LiCl (12% RH), MgCl 2 (33%), NaCl (75%) and KCl (84%), which were prepared by dissolving excess amounts of salts in deionised water 30,36 . A humidity meter was used inside the container to check that the salts provided the literature values of RH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GO membranes with different IL spacing were prepared by storing them in a sealed container with different RH of 0%, 12%, 33%, 75%, 84% and 100%. To this end, we used saturated solutions of LiCl (12% RH), MgCl 2 (33%), NaCl (75%) and KCl (84%), which were prepared by dissolving excess amounts of salts in deionised water 30,36 . A humidity meter was used inside the container to check that the salts provided the literature values of RH.…”
Section: Methodsmentioning
confidence: 99%
“…Graphene oxide (GO) has previously been suggested as a 2D-surfactant to prepare stable dispersions of graphite and carbon nanotubes (CNTs) in water 29,30 . Here, graphene oxidegraphene (GO-Gr) aqueous dispersions were prepared by exfoliating graphite in water using GO as a surfactant.…”
Section: Swelling-controlled Graphene Oxide-graphene (Go-gr)membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, control of graphite oxidation is necessary for various applications of graphene oxide sheets. It was recently reported that graphene oxide sheets with different oxygen content amounts can be prepared simply by changing the starting graphite, oxidation time, and amount of oxidant, providing variation in the size distribution, electrical conductivity, and energy band gap [21][22][23][24]. However, no correlation between the properties or size of graphene oxide sheets and the oxidation temperature has been reported thus far.…”
Section: Degree Of Oxidation Of Graphitementioning
confidence: 99%
“…72 These structures are 2-3 nm in diameter, have two or three p-stacked PAH moieties comprising the core, and an oxygen-rich corona. 73 The optical properties of these structures are highly dependent on particle size; the absorption maxima red-shifts with increased particle size, while emission wavelength depends on the excitation energy, possibly due to variation in the density of defect sites associated with sp 2 carbons.…”
Section: Nanoscale Assembly T Emrick and E Pentzermentioning
confidence: 99%